Antibacterial and Antioxidant Activity of Red Melinjo (Gnetum gnemon L.) Peel Ethanolic Extract - Caroline Caroline; Adolf Parhusip; Nuri Arum Anugrahati; Yusuf Cendrawan (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2026)
Melinjo (Gnetum gnemon L.) is a common native plant in Southeast Asia. The peel of Melinjo fruit has not been fully utilized. The phenolic, flavonoid compounds and vitamin C of the melinjo peel can potentially be antimicrobial and antioxidant agents, with the red peel of ripe melinjo having the highest content than that of unripe yellow and green peel. The red melinjo peel was extracted using ethanol through maceration. Antimicrobial activity was tested by well diffusion using various microorganisms and extract concentrations (0–16%), while antioxidant activity was assessed over different storage periods (0–12 days). The purpose of this research was to assess whether red melinjo peel extract could function as an antimicrobial and antioxidant source. The ethanol-based extract at 12% successfully suppressed B. cereus, P. aeruginosa, and E. coli, but failed to inhibit R. oligosporus. Its antioxidant capacity was confirmed, with an IC₅₀ of 702.99 mg/L on day zero, followed by a decrease as storage duration progressed.